Predictors of Long-term Outcome in Patients with Acute Coronary Syndrome Undergoing Percutaneous Coronary Intervention: A single center registry (THCR) - Seyed Ebrahim Kassaian; Mohammad Sahebjam; Mojtaba Salarifar; Mohammad Alidoosti; Alimohammad Haji Zeinali; Davood Kazemi Saleh; Hamidreza Poorhoseini; Navid Paydari; Gholamreza Davoodi; Mehran Mahmoodian; Seyed Hesameddin Abbasi (Journal of Tehran University Heart Center, 2006)
Background: This study sought to access differences in long-term (9 months) outcomes between Acute Coronary Syndrome (ACS) patients who undergo early intervention compared to Percutaneous Coronary Intervention (PCI) in stable and refractory conditions.